What fecal analyses reveal about Manniophyton fulvum consumption in LuiKotale bonobos (Pan paniscus): A medicinal plant revisited. Issue 4 (21st August 2021) - Kreyer, Mélodie; Stewart, Kathrine; Pashchevskaya, Sonya; Fruth, Barbara
Abstract: Observations of animals in the wild can result in the discovery of plants for human medicinal purposes. In this context, our closest relatives, the great apes, are of particular interest. The Euphorbiaceae Manniophyton fulvum possesses both phytochemical and biomechanical properties. Its use in the genus Pan ( P. troglodytes; P. paniscus ) is thought to be based on its mechanical properties promoting the egestion of intestinal parasites, but additional observations from different habitats where the behavior is performed may shed more light on its true purpose. To improve our understanding of what triggers this behavior, we investigated M. fulvum consumption in wild bonobos at LuiKotale, Democratic Republic of the Congo between December 2018 and July 2020. Specifically, we tested the hypothesis that M. fulvum ingestion is related to gastro‐intestinal parasite expulsion. Of 649 focal follows of 37 individuals from two habituated communities, consumption of M. fulvum was observed on 111 days ( N = 507), independent of seasons, environmental factors and the plant's availability. A total of 588 fecal samples were assessed for the presence/absence of gastro‐intestinal parasites. We found strongyle eggs in 2.89% of samples and their presence was not associated with the ingestion of M. fulvum or environmental conditions. We discuss the importance of seasonality in the life cycle of strongyle species that may influence the pattern of M. fulvum consumption observed at LuiKotale. Our data open additional perspectives concerning behavioral parameters such as the existence of a cultural component when comparing ingestion behavior between communities. Research highlights: The egestion of strongyles and cestodes was not predicted by the ingestion and/or egestion of M. fulvum leaves and stem strips Results from the present study and previous studies suggest a role of the climate in the host/parasite dynamic that may affect the behavior pattern Differences observed between bonobo communities suggest the existence of a behavioral culture in M. fulvum consumption Abstract : LuiKotale seasonality (December 2018–July 2020) with cumulative monthly rain (blue) and mean minimum temperature (red) linked to M. fulvum ingestion and strongyle egg presence by month; Bonobo ingestion bouts of M. fulvum (dots) and presence of strongyle eggs in feces (crosses) observed